Fundamentals of Ocean Acoustics - Brekhovskikh, L. M. (Modern Acoustics and Signal Processing, 2003)
This book provides an up-to-date introduction to the theory of sound propagation in the ocean. The text treats both ray and wave propagation and pays considerable attention to stochastic problems such as the scattering of sound at rough surfaces and random inhomogeneities. An introductory chapter that discusses the basic experimental data complements the following theoretical chapters. New material has been added throughout for this third edition. New topics covered include: - inter-thermocline lenses and their effect on sound fields - weakly divergent bundles of rays - ocean acoustic tomography - coupled modes - sound scattering by anisotropic volume inhomogeneities with fractal spectra - Voronovich's approach to sound scattering from the rough sea surface. In addition, the list of references has been brought up to date and the latest experimental data have been included.